Anselm of Canterbury: communities, contemporaries and criticism - Healy-Varley, Margaret; Gasper, Giles E. M.; Younge, George (Anselm studies and texts, 2022)
This volume explores the work of Anselm of Canterbury, theologian and archbishop, in light of the communities in which he participated. Featuring thirteen essays from leading historians, theologians, and literary scholars, the collection ranges from Anselm's immediate contemporaries to the reception of his work, and formation of his posthumous reputation, by later medieval readers. Individual essays consider the role of friendships in his career, his relations with students, correspondence with women, interventions in the political sphere, and influence as leader of the monastic communities at Bec and Canterbury. Together, these essays present a new profile of the archbishop, revealing an individual whose work emerged from a vibrant culture of debate, criticism, and collaboration